Eigenfunctions of the Cosine and Sine Transforms - Katsnelson, V. (Журнал математической физики, анализа, геометрии, 2013)
A description of the eigensubspaces of the cosine and sine operators is given. The spectrum of each of these two operators consists of two eigen- values 1, -1 and their eigensubspaces are infinite{dimensional. There are many possible bases for these subspaces, but most popular are the ones constructed from the Hermite functions. We present other "bases" which are not discrete orthogonal sequences of vectors, but continuous orthogo- nal chains of vectors. Our work can be considered to be a continuation and further development of the results obtained by Hardy and Titchmarsh: "Self-reciprocal functions"(Quart. J. Math., Oxford, Ser. 1 (1930)). Представлено описание собственных подпространств косинус- и синус-опе- раторов. Спектр каждого из этих двух операторов состоит из двух собственных значений 1, -1 , а их собственные подпространства бесконечномерные. Есть много возможных базисов этих подпространств, но наиболее популярными являются те, которые построены из функций Эрмита. Мы представляем другие "базисы", которые являются не дискретными ортогональными последовательностями векторов, а непрерывными ортогональными цепочками векторов. Работу можно считать продолжением и дальнейшим развитием результатов, приведенных Харди и Титчмаршем в статье "Self-reciprocal functions" (Quart. J. Math., Oxford Ser. 1 (1930)).